2018
DOI: 10.1155/2018/5637042
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Lebesgue Points for Hajłasz Functions

Abstract: Let X be a quasi-Banach function space over a doubling metric measure space P. Denote by α X the generalized upper Boyd index of X. We show that if α X < ∞ and X has absolutely continuous quasinorm, then quasievery point is a generalized Lebesgue point of a quasicontinuous Haj lasz function u ∈Ṁ s,X . Moreover, if α X < (Q + s)/Q, then quasievery point is a Lebesgue point of u. As an application we obtain Lebesgue type theorems for Lorentz-Haj lasz, Orlicz-Haj lasz and variable exponent Haj lasz functions.(1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…where t > Q/(Q + s) and 0 < s ′ < s, is known to hold. The estimate (3.8) can be proven using a chaining argument and a Sobolev-Poincaré type inequality from [9], see [16,Lemma 4.2]. Somewhat surprisingly, with medians, a better estimate (3.7) follows by a completely elementary argument.…”
Section: Lemmasmentioning
confidence: 99%
See 1 more Smart Citation
“…where t > Q/(Q + s) and 0 < s ′ < s, is known to hold. The estimate (3.8) can be proven using a chaining argument and a Sobolev-Poincaré type inequality from [9], see [16,Lemma 4.2]. Somewhat surprisingly, with medians, a better estimate (3.7) follows by a completely elementary argument.…”
Section: Lemmasmentioning
confidence: 99%
“…Property (8) above says that medians of small balls behave like integral averages of locally integrable functions on Lebesgue points. Recently, in [16], it was shown that for Haj lasz-Besov and Haj lasz-Triebel-Lizorkin functions, the limit in (8) exists outside a set of capacity zero. Note also that if u ∈ L p (A), p > 0, then by properties (7) and (8),…”
Section: Lemmasmentioning
confidence: 99%
“…As u has certain regularity, one would expect a smaller exceptional set than that of usual locally integrable functions. Inspired by [41,45], we introduce capacities related, respectively, to M φ p,q (X) and N φ p,q (X) to measure such exceptional sets.…”
Section: Remark 3 (I)mentioning
confidence: 99%
“…Let u ∈ L 0 (X). Recall that a point x ∈ X is called a generalized Lebesgue point of u if (56) holds true for x and any γ ∈ (0, 1/2]; see, for instance [41,44,45]. If u is locally integrable, as was pointed by ( [46], p. 231), any Lebesgue point of u is a generalized Lebesgue point of u.…”
Section: Lemma 12mentioning
confidence: 99%
See 1 more Smart Citation